Promoting Technological Entrepreneurship through Sustainable Engineering Education. (2016) - Cristina, Momete Daniela
Abstract: The main purpose of this paper is to identify appropriate solutions considered essential for the implementation of an authentic sustainable engineering education for the students in engineering. This is completed with the aim to increase the adaptation of the graduates in engineering to a competitive and dynamic economy, characterized by the attributes of sustainable development and the current society needs and has in view Romania's situation. The paper introduces new solutions for the promotion of technological entrepreneurship and also presents the original inventory of qualities needed for a student in engineering to become an authentic technopreneur. The findings of this paper have the potential to help graduates in engineering to be able to develop their innovative side, being better "equipped" to become technological entrepreneurs or intrapreneurs.